Study of thermal diffusivity of liquid reduced graphene oxide using thermal wave resonant cavity technique - Kinsu, Rosno (2017)
Graphene oxide (GO) exhibit excellent thermal properties where it has ability to diffuse heat efficiently. By reducing the GO to the reduced graphene oxide (rGO), the thermal diffusivity (TD) can be enhanced. The aim of study are to measure various standard liquid thermal diffusivities by employing a Thermal Wave Resonant Cavity (TWRC) technique, and secondly to study the thermal, optical property as well as morphology of rGO fabricated by ultra violet (UV) and Nd:YAG laser radiations at various exposure time. In order to achieve the first objective, the liquid thermal diffusivities (water, glycerol and ethylene glycol) were measured by using the TWRC technique and calculated via a normalisation procedure. For this, a control program in LabView programming language was written to automate the setup in measuring the TD. For the second objective, it was achieved by reducing GO in water suspension with UV and Nd:YAG laser irradiation. The thermal, optical, morphological properties of it were investigated by TWRC technique, UV-Vis spectroscopy, X-Ray Photoelectron Spectroscopy (XPS), and a Field-emission Scanning Electron Microscopy (FeSEM). Without the normalization process on the TWRC technique, TD of standard liquid water obtained by the cavity scan is 1.431×10-3 and 1.435×10-3 cm2s-1 for phase and amplitude, respectively, and very close to literature (0.5%). This shows that the current TWRC set up is reliable enough and can be used to measure liquid TD. With the normalisation process, TD of water with for frequency scan of amplitude signal with respect to literature improves tremendously to 1.6% but with a little increase for that of phase signal, 3.5%. For cavity scan, TD of water for amplitude signal and for phase are 0.6% and 1.9%, respectively, with respect to literature which are very small indeed. Over all this agrees with the first hypothesis. The TD measurement revealed that the rGO produced with UV radiation has higher value compared to that of with laser. The trend is apparent when the irradiation time increased. Accordingly, its TD decreased at higher rGO concentration. FeSEM images revealed that the UV radiation reduced graphene oxide (UVrGO) sample has more ripples, deeper wrinkles, and fluffier texture compared to that of laser reduced graphene oxide (LrGO). The coarser rGO surface suggests the higher rate of reduction. The UV-Vis peak of UVrGO has shifted further to red than that of LrGO, complimenting morphology results. The XPS survey analysis showed that atomic concentration of carbon increases whilst the concentration of carbon containing C-O, and C=O group decreases. Hence, verifying the reduction of GO to rGO. As a conclusion, exposing GO to UV or laser radiation will reduce it to rGO, consequently increasing its TD. The reduction rate was highly influenced by type of treatment and exposure time. It was found that UVrGO give higher reduction rate and higher increase in TD when the exposure time increased as compared to LrGO. These findings have given a promising future for rGO to be further studied as an alternative to conventional liquid conductors.